2010
DOI: 10.1128/mcb.01520-09
|View full text |Cite
|
Sign up to set email alerts
|

PHF8 Targets Histone Methylation and RNA Polymerase II To Activate Transcription

Abstract: Mutations in PHF8 are associated with X-linked mental retardation and cleft lip/cleft palate. PHF8 contains a plant homeodomain (PHD) in its N terminus and is a member of a family of JmjC domain-containing proteins. While PHDs can act as methyl lysine recognition motifs, JmjC domains can catalyze lysine demethylation. Here, we show that PHF8 is a histone demethylase that removes repressive histone H3 dimethyl lysine 9 marks. Our biochemical analysis revealed specific association of the PHF8 PHD with histone H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
105
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 55 publications
13
105
0
Order By: Relevance
“…Based on in vitro demethylation assays Loenarz et al first reported that PHF8 catalyzed demethylation of H3K9me2/1, H3K27me2 and H3K36me2 [28]. Other studies show PHF8 as a predominant H3K9me2/1 demethylase with either minimal H3K27me2 and H3K36me2 demethylase activity [29] or H3K9me2/1 demethylase activity only [30][31][32][33]. In agreement with the latter studies, we showed that in all assays PHF8 exhibited histone demethylase activity with H3K9me2/1 specificity.…”
Section: Discussionsupporting
confidence: 68%
“…Based on in vitro demethylation assays Loenarz et al first reported that PHF8 catalyzed demethylation of H3K9me2/1, H3K27me2 and H3K36me2 [28]. Other studies show PHF8 as a predominant H3K9me2/1 demethylase with either minimal H3K27me2 and H3K36me2 demethylase activity [29] or H3K9me2/1 demethylase activity only [30][31][32][33]. In agreement with the latter studies, we showed that in all assays PHF8 exhibited histone demethylase activity with H3K9me2/1 specificity.…”
Section: Discussionsupporting
confidence: 68%
“…The observed ratio of few upregulated to many downregulated genes was in line with the suggested positive coactivator function of PHF8 (Fortschegger et al, 2010). Functional annotation of the 62 downregulated genes showed significant enrichment of the integrin signaling pathway.…”
Section: Phf8 Regulates Motility-related Gene Expression Patterns In supporting
confidence: 76%
“…A more detailed analysis of potential PHF8 target genes involved in PrCa cell migration may be an important area for future investigation, and to elucidate the functional mechanisms PHF8 is involved in. Interestingly, PHF8 was found to bind to the integrin beta-1 promoter, and linked to positive regulation of genes related to focal adhesion in HeLa cells (Fortschegger et al, 2010). PHF8 silencing also reduced proliferation and mildly inhibited G1-S phase transition, which is in line with a suggested role of PHF8 in cell cycle progression (Feng et al, 2010;Liu et al, 2010).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Interestingly, LP strongly upregulated the gene expression of two chromatin modifying enzymes: EHMT2, a histonelysine N-methyltransferase, and PHF8, a histone demethylase, which were shown to act on histone 3 (Fortschegger et al 2010;Fritsch et al 2010). Upregulation of EHMT2 could be observed after treatment with all three strains compared to Inflamed tissue.…”
Section: Discussionmentioning
confidence: 96%